2014
DOI: 10.4314/ajtcam.v11i3.17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polysaccharides from <i>Gynostemma Pentaphyllum</i> (Thunb.), Makino on Physical Fatigue

Abstract: Background: Gynostemma pentaphyllum (Thunb.) Makino has been reported to have a wide range of health benefits in Chinese herbal medicines. Polysaccharides from Gynostemma pentaphyllum (PGP), has been identified as one of the active ingredients responsible for its biological activities. Although many pharmacological activities of PGP have received a great deal of attention, there is limited evidence for the anti-fatigue effects of PGP. The purpose of this study was to investigate the effects of polysaccharides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Polysaccharides are one of the most abundant components of G. pentaphyllum and represent a major group of biologically active constituents. G. pentaphyllum polysaccharides isolated with different extraction and purification methods have been shown to be structurally diverse biomacromolecules with various functions, including anti-inflammatory [ 18 ], antitumor [ 19 ], immunomodulatory [ 20 , 21 ], and antioxidant activities [ 22 ], antiexercise fatigue properties [ 23 , 24 ], hepatoprotective [ 25 ], and neuroprotective [ 26 ] activities and as a therapeutic agent for the treatment hyperlipidemia disorders [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides are one of the most abundant components of G. pentaphyllum and represent a major group of biologically active constituents. G. pentaphyllum polysaccharides isolated with different extraction and purification methods have been shown to be structurally diverse biomacromolecules with various functions, including anti-inflammatory [ 18 ], antitumor [ 19 ], immunomodulatory [ 20 , 21 ], and antioxidant activities [ 22 ], antiexercise fatigue properties [ 23 , 24 ], hepatoprotective [ 25 ], and neuroprotective [ 26 ] activities and as a therapeutic agent for the treatment hyperlipidemia disorders [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the blood TG and glucose or glycogen levels in the muscle and liver are important indices of maintenance performance, which can delay physical fatigue [ 41 ]. These effects of G. pentaphyllum on enhanced exercise performance have been reported with polysaccharides and gypenosides [ 3 4 24 ]. Wang et al [ 3 ] reported that G. pentaphyllum polysaccharide supplementation could increase the swimming exhaustion time and liver glycogen content and reduce oxidative stress.…”
Section: Discussionmentioning
confidence: 67%
“…Makino is an herbaceous vine plant of the family Cucurbitaceae , whose leaves are used for traditional tea or oriental herb medicine in Asia [ 3 ]. G. pentaphyllum has been prescribed traditionally for clearing heat, detoxification, dry cough, and chronic bronchitis [ 4 ]. Several studies have reported that G. pentaphyllum has important biological activities, including anti-oxidant [ 5 ], anti-inflammatory [ 6 7 8 ], hypoglycemic [ 9 ], hypolipidemic [ 10 11 12 ], anti-obesity [ 13 ], anti-diabetic [ 14 ], neuroprotective [ 15 ], and anti-cancer properties [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endurance-swimming time, forelimb-grip strength, and changes in biochemical marker levels were studied and a histological analysis of muscle and other tissues was performed to assess the fatigue in animal models [ 24 , 25 ]. Endurance-swimming time in a forced-swimming test, forelimb-grip test, and rotary rod test have been widely used in animal models for evaluating the anti-fatigue efficacy of drugs or natural compounds [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%